Picture this! Boosting ESL writing with storyboards - Aris, Haziqah Zulaikha; Hussain, Annur Najiah Hussaini; Shamsuddin, Aizat (Kulliyyah of Education, International Islamic University Malaysia., 2025)
This study explores the use of storyboard templates as a visual learning tool to support ESL students in writing the CEFR-aligned PT3 English Essay (Part 1). Storyboarding allows students to visualize, plan, and organize their ideas in sequence, enabling them to write with greater confidence, clarity, and creativity. Rooted in cognitive and constructivist learning theories and aligned with the multiliteracies approach, the storyboard method promotes student-centered, multimodal engagement in the writing classroom. A qualitative research design was employed, with data collected through semi-structured interviews to investigate students’ perceptions and the impacts of using storyboard in their writing process. Thematic analysis revealed three key findings: (1) improved writing skills, particularly in structure and fluency, (2) enhanced confidence and time management, and (3) mixed reactions regarding limited writing space and constrained idea expression due to fixed visuals. While many students found the storyboard helpful as a guide for organizing ideas and managing time, some felt restricted by the predetermined images and limited space for elaboration. Vocabulary limitations also affected their ability to fully articulate their thoughts, especially when unfamiliar visuals were used. Despite these challenges, most students acknowledged the storyboard’s usefulness in supporting idea generation and essay planning. They also suggested expanding its use to other subjects, such as Malay Language and History, to enhance comprehension and narrative skills across disciplines. This study contributes to the field of ESL writing instruction by highlighting the pedagogical value of visual tools. Storyboarding offers a practical shift from conventional text-heavy methods to a more accessible and engaging model. However, its effectiveness depends on thoughtful implementation, particularly in designing flexible templates and selecting culturally appropriate visuals that support, rather than constrain, learners' expression.